Celtic Arthurian material - Lloyd-Morgan, Ceridwen (Boydell & Brewer, 2004)
A special number devoted to Celtic material. This special number of the well-established series 'Arthurian Literature' is devoted to Celtic material. Contributions, from leading experts in Celtic Studies, cover Welsh, Irish and Breton material, from medieval texts to oral traditions surviving into modern times. The volume reflects current trends and new approaches in this field whilst also making available in English material hitherto inaccessible to those with no reading knowledge of the Celtic languages. CERIDWEN LLOYD-MORGAN has published widely in the field of Arthurian studies. She is currently Honorary Research Fellow in the School of Welsh, Cardiff University